Penerapan Analogi Kapal Galleon pada Museum Bahari Aceh di Sabang - Irfan Saptadi (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
The Maritime Museum is a comprehensive way to provide insight into historical education and to keep the results of developments and also other objects related about Aceh's nautical culture. This building was designed with the principle of awakening from Aceh's maritime potential, thus applying a cultural symbol in the form of a combination of Galleon ships. These characteristics are manifested in the design with firm and clear elements, both in the processing of shapes and the application of layout space patterns. Location of the placement  the building itself is also on the Sabang island, one of the symbols of maritime in the international shipping world during the Dutch Government. With these historical records, as well as locations close to the sea provide hard challenges as well as more potential for this Maritime Museum object. The concept divided into two floors with an open plan system is also adapted to suit the needs and also concepts of the ship.